2018
DOI: 10.3762/bjoc.14.128
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent organoiodine compounds: from reagents to valuable building blocks in synthesis

Abstract: Most of the polyvalent organoiodine compounds derive from iodoarenes, which are released in stoichiometric amounts in any reaction mediated by λ3- or λ5-iodanes. In parallel to the development of solid-supported reagents or reactions catalytic in iodine, a third strategy has emerged to address this issue in terms of sustainability. The atom-economy of transformations involving stoichiometric amounts of λ3- or λ5-iodanes, thus, has been improved by designing tandem reactions that allows for incorporating the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 114 publications
0
33
0
Order By: Relevance
“…Scheme 2. Initial rates for conversion of N-allylbenzamide 1 into oxazoline 3 with iodoarene precatalysts 4-10, determined by 1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 2. Initial rates for conversion of N-allylbenzamide 1 into oxazoline 3 with iodoarene precatalysts 4-10, determined by 1…”
Section: Resultsmentioning
confidence: 99%
“…Hypervalent iodine chemistry has continued to receive considerable attention from synthetic practitioners over the past decades with a wide variety of useful reactivities revealed. 1 Hypervalent iodine compounds can possess reactivity profiles comparable to some heavy metal and transition metal complexes but may not suffer from disadvantages such as toxicity, cost or scarcity. In particular, the ability to access reactive  3 -iodanes in-situ from iodoarenes and an oxidant has permitted the discovery of a range of reactions that are catalytic in iodoarene.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, sustainable processes have been developed such as tandem reactions involving a second step that enables the capture of the in-situ-generated aryl iodide side-compound. Even if tandem reactions including various sequences combining oxidation reactions or nucleophilic additions are widespread [130], tandem catalytic couplings on heteroarenes are really sparse and still remain a great challenge. Although decarboxylative cross-coupling reactions are not covered in this review, it is worth mentioning two recent reports from the group of Zhang who reported the tandem π-extended decarboxylative annulation [131,132].…”
Section: Atom-economical Tandem N-h/ch Arylation Of Heteroarenesmentioning
confidence: 99%
“…[73] The released benzoate 31 acts as a nucleophile, resulting in perfect atom economy, which is rare in hypervalent iodine chemistry. [74,75] The copper (I) catalyst is believed to activate the iodine(III) reagent and accelerate the formation of a reactive episulfonium intermediate I.…”
Section: )mentioning
confidence: 99%